Search for high-mass resonances decaying to dilepton final states in pp collisions at √s = 7 TeV with the ATLAS detector - Anduaga, Xabier Sebastián (2012)
The ATLAS detector at the Large Hadron Collider is used to search for highmass resonances decaying to an electron-positron pair or a muon-antimuon pair. The search is sensitive to heavy neutral Z′ gauge bosons, Randall-Sundrum gravitons, Z∗ bosons, techni-mesons, Kaluza-Klein Z/γ bosons, and bosons predicted by Torsion models. Results are presented based on an analysis of pp collisions at a center-of-mass energy of 7TeV corresponding to an integrated luminosity of 4.9 fb−1 in the e+e− channel and 5.0 fb−1 in the μ+μ−channel. A Z′ boson with Standard Model-like couplings is excluded at 95% confidence level for masses below 2.22 TeV. A Randall-Sundrum graviton with coupling k/MPl = 0.1 is excluded at 95% confidence level for masses below 2.16 TeV. Limits on the other models are also presented, including Technicolor and Minimal Z′ Models.